Effects of Decalcifying Agents of Variable Duration on PD-L1 Immunohistochemistry. Issue 2 (11th October 2019) - Strickland, Amanda L; Blacketer, Sara; Molberg, Kyle; Markantonis, John; Lucas, Elena
Abstract: Objectives: To evaluate the effects of decalcifying agents on programmed cell death ligand 1 (PD-L1) immunohistochemistry (IHC). Methods: Fragments of 10 placentas (high PD-L1 expressor) and 10 lungs (lower PD-L1 expressor) were formalin-fixed and subjected to four decalcifying solutions (EDTA, formic acid/MasterCal IM Plus [FA/MC], 12% HCl, and Decal STAT/23% HCl) for 1, 2, 6, or 24 hours. H&E staining and PD-L1 using IHC 22C3 pharmDx were performed, and PD-L1 staining was assessed. Results: Minimal to no change in staining intensity or proportion of stained cells was seen with EDTA or FA/MC at all decalcifying durations. Both HCl-based decalcifiers demonstrated a progressive decrease in percentage of positive cells and staining intensity with longer decalcifying duration, particularly with Decal STAT. Conclusions: EDTA and FA/MC have little effect on PD-L1 expression. 12% HCl causes a progressive decline in staining. Decal STAT dramatically reduced staining with all treatment durations, especially at 24 hours.